Plasma Complement 3 and Complement 4 Are Promising Biomarkers for Distinguishing NMOSD From MOGAD and Are Associated With the Blood-Brain-Barrier Disruption in NMOSD - Lin, Liuyu; Wu, Yuqing; Hang, Hailun; Lu, Jie; Ding, Yuanliang (Frontiers in Immunology, 2022)
Background and Objective Neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody (MOG-IgG) associated disease (MOGAD) are autoimmune inflammatory demyelinating diseases of the central nervous system (CNS). As the clinical features of NMOSD are similar to MOGAD, diagnostic confusion exists between the two diseases. To better discriminate NMOSD from MOGAD, we investigated whether the plasma levels of complement 3 (C3) and complement 4 (C4) are different in NMOSD and MOGAD during the acute attacks of the diseases. We sought to determine whether C3 or C4 has an influence on the features of NMOSD. Methods In this observational study, data from 73 aquaporin-4 antibodies (AQP4-IgG) positive NMOSD patients and 22 MOG-IgG positive MOGAD patients were collected retrospectively. Demographics, clinical characteristics, plasma parameters, and cerebrospinal fluid (CSF) findings will be analyzed for comparability between the two groups. Immunoglobulin-G (IgG) and albumin were measured in both plasma and CSF. Plasma levels of C3 and C4 were measured and compared between the NMOSD, MOGAD, and 42 healthy controls (HC). The correlations between plasma C3, C4, and NMOSD clinical parameters were analyzed. Results The ages of onset were later in the AQP4-IgG positive NMOSD group and females predominated, which differed from the MOGAD group, whose ages were younger and with a slight male preponderance. The AQP4-IgG positive NMOSD patients presented with the clinical symptoms of optic neuritis (ON) and transverse myelitis (TM), whereas encephalitis symptoms were more prevalent in MOGAD patients. CSF analysis shows that slight but not significantly higher white cell count (WCC) and protein were observed in the MOGAD group than in the AQP4-IgG positive NMOSD group. The plasma levels of IgG in MOGAD patients are significantly lower (p = 0.027) than in NMOSD patients. On the contrary, the plasma levels of albumin in MOGAD were higher than in NMOSD, which reached statistical significance (p = 0.039). Both the plasma C3 and C4 levels in the NMOSD group were significantly lower than in MOGAD and HC. The receiver operating characteristic (ROC) curve of the prediction model comprises C3 and C4 to distinguish NMOSD from MOGAD [area under the curve (AUC): 0.731, 0.645], which are considered to have discriminatory values. The results of Spearman’s analysis revealed that there was a significant positive correlation between the plasma C3 and the CSF WCC (r = 0.383, p = 0.040). There was an inverse correlation between plasma C4 and plasma IgG (r = -0.244, p = 0.038). Plasma C3 or C4 was significantly positively correlated with CSF albumin and Q-Alb, which is considered a measure of blood-brain barrier (BBB) disruption. Conclusion During the acute phase of NMOSD and MOGAD, plasma C3 and C4 may become potential biomarkers for distinguishing the two diseases and reflecting the NMOSD BBB damage.